Feminist Pedagogy: Deconstructing Patriarchal Culture (20 Years Reflection of Activism inside and outside of Classroom) - Arivia, Gadis (Jurnal Perempuan, 2016)
This paper explores feminist pedagogy from the author’s experience, working as both an academic and activist in the women’s movement. The author does not separate pedagogy from personal experiences inside and outside the classroom. Feminist educators have a passion for their teaching and demand change. They demand confrontations and interruptions. This paper is an adventure in self-reflection of how the author’s experience as an activist affect teachings in the classrooms and how as an academic impact the public space. Many changes are needed in Indonesia’s higher education system, one of which makes the campus as a safe place, free from harassment and sexual violence, and diversity in sexual orientation.